English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-06 06:30:09 · 12 answers · asked by Redbone Diva 1 in Science & Mathematics Mathematics

12 answers

{(6+4)(5+5)}-(25x2)
=(10x10)-(50)
=100-50
=50

2007-09-06 06:35:28 · answer #1 · answered by alpha 7 · 0 0

((6+4) * (5+5)) - (25 * 2)
= (10 * 10) - 50
= 100 - 50
= 50.

2007-09-06 13:33:59 · answer #2 · answered by RustyL71 4 · 0 0

50

2007-09-06 13:34:32 · answer #3 · answered by piffingod 2 · 0 0

50

2007-09-06 13:38:16 · answer #4 · answered by sv1973 2 · 0 1

First, do the math inside the parentheses:
((6 + 4)(5 + 5)) - (25 x 2)
((10)(10)) - 50, or
(10 x 10) - 50
Then do the rest of the math:
100 - 50
50

2007-09-06 13:37:49 · answer #5 · answered by Wile E. 7 · 0 1

= (10) (10) - 50
= 100 - 50
= 50

2007-09-06 15:24:38 · answer #6 · answered by Como 7 · 2 1

(10*10)-50=100-50=50

2007-09-06 13:33:25 · answer #7 · answered by WattyIrma 3 · 0 0

( (10)*(10) ) - 50=100-50=50

2007-09-06 13:36:35 · answer #8 · answered by Vimal 1 · 0 1

It should be ((6+4)x(5*5))-(25x2)=50

2007-09-06 13:40:27 · answer #9 · answered by Garden Lady 1 · 0 1

(10)(10) - (50) = 50

2007-09-06 13:38:28 · answer #10 · answered by libraboy28 2 · 0 1

fedest.com, questions and answers